Assignment of the molecular origins of CEST signals at 2 ppm in rat brain. Issue 3 (26th June 2017) - Zhang, Xiao‐Yong; Xie, Jingping; Wang, Feng; Lin, Eugene C.; Xu, Junzhong; Gochberg, Daniel F.; Gore, John C.; Zu, Zhongliang
Abstract : Purpose: Chemical exchange saturation transfer effects at 2 ppm (CEST@2ppm) in brain have previously been interpreted as originating from creatine. However, protein guanidino amine protons may also contribute to CEST@2ppm. This study aims to investigate the molecular origins and specificity of CEST@2ppm in brain. Methods: Two experiments were performed: (i) samples containing egg white albumin and creatine were dialyzed using a semipermeable membrane to demonstrate that proteins and creatine can be separated by this method; and (ii) tissue homogenates of rat brain with and without dialysis to remove creatine were studied to measure the relative contributions of proteins and creatine to CEST@2ppm. Results: The experiments indicate that dialysis can successfully remove creatine from proteins. Measurements on tissue homogenates show that, with the removal of creatine via dialysis, CEST@2ppm decreases to approximately 34% of its value before dialysis, which indicates that proteins and creatine have comparable contribution to the CEST@2ppm in brain. However, considering the contribution from peptides and amino acids to CEST@2ppm, creatine may have much less contribution to CEST@2ppm. Conclusions: The contribution of proteins, peptides, and amino acids to CEST@2ppm cannot be neglected. The CEST@2ppm measurements of creatine in rat brain should be interpreted with caution. Magn Reson Med 78:881–887, 2017. © 2017 International Society for Magnetic Resonance in Medicine.